Torture by the Nigerian Police Force: International Obligations, National Responses and the Way Forward - Babatunde, Elkanah (Strathmore Law Review, 2017)
Police brutality has become rife in Nigeria and is regarded by some as a normal part of police operations. This is despite the fact that the Nigerian Constitution provides for the guarantee of the right to dignity and the protection against torture and inhuman or degrading treatment. Nigeria is also party to some international treaties such as the International Covenant on Civil and Political Rights, the Convention against Torture and other Cruel, Inhuman or Degrading Treatment or Punishment and the African Charter on Human and Peoples’ Rights which expressly prohibit torture and other cruel, inhuman and degrading treatment. This raises the question whether police brutality in Nigeria amounts to torture and / or other cruel, inhuman or degrading treatment and whether the existing legal framework sufficiently prevents and punishes the perpetrators of these acts.